Timing of Delivery in Pregnancies Complicated by Suspected Fetal Growth Restriction without Doppler Abnormalities - Pineles, Beth L.; Crimmins, Sarah; Turan, Ozhan (American Journal of Perinatology, 2020)
Objective This study aimed to identify the optimal gestational age for delivery of pregnancies complicated by fetal growth restriction (FGR) without Doppler abnormalities.Study Design Cases of FGR (ultrasound-estimated fetal weight less than the 10th or abdominal circumference less than the 5th percentile for gestational age) without fetal Doppler abnormalities were identified from a fetal ultrasound database. The primary outcome was a composite of perinatal mortality and morbidity. The risk of the primary outcome for each gestational age was compared with pregnancies delivered at 390/7 to 406/7 weeks. Odds ratios were adjusted for potential confounders.Results The analysis included 1,024 pregnancies. FGR was identified at a median of 235/7 weeks (range: 20–42 weeks). Four cases of fetal death (234/7—376/7 weeks) and no neonatal deaths were included. The primary outcome occurred in 209 patients (20.4%). This was greater for patients delivered at less than 37 weeks' gestation than for those delivered at or after 39 weeks' gestation, with no increased risk after 40 weeks.Conclusion Among pregnancies complicated by suspected FGR without Doppler abnormalities, delivery at 39 weeks is safe with no difference in perinatal outcomes from 37 to 42 weeks.
Keywords: fetal death; fetal growth restriction; IUGR; stillbirth